2016
DOI: 10.1128/jcm.02998-15
|View full text |Cite
|
Sign up to set email alerts
|

Improved Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry (MALDI-TOF MS)-Based Identification of Mycobacterium spp. by Use of a Novel Two-Step Cell Disruption Preparatory Technique

Abstract: Ireland bT he use of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has been widely implemented for microbial identification in clinical microbiology in recent years. This development can be attributed to its low operating cost and to its speed and reliability of identification for many bacteria and fungi. However, the use of MALDI-TOF MS for mycobacteriology has been less satisfactory, mainly owing to nonstandardized preparatory methods, poor reproducibility, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike most bacteria, mycobacteria require prior inactivation and disruption of the mycolic acid-rich cell wall, both for biosafety reasons and to liberate the cellular protein content. Numerous suitable procedures have been proposed, combining heat-killing, ethanol, sonication, and/or silica-based bead beating preceding the regular formic acid/acetonitrile extraction (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The reported success rates vary between 55% and 98% correct species-level identifications, but the large variety in strain collections, culture conditions, extraction protocols, hardware, and databases hinder data comparison between publications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar prospective study on Vitek MS would be helpful to define real performances of IVD v3.0 from primary cultures of respiratory samples. Several authors recently described new extraction protocols (12,18,40,41), which could increase the ratio of mycobacterial proteins to patients' proteins and probably improve the identification rates at the time of detection.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is quite simple and cost-effective (8) and allows rapid identification of organisms on the basis of spectral fingerprints produced by extracted proteins. It was initially evaluated with mycobacterial intact cells (9)(10)(11)(12), but several investigators worked on improving inactivation and protein extraction (13)(14)(15)(16)(17)(18)(19)(20). Most published studies assessed the performance of MALDI-TOF BioTyper (Bruker Daltonics, Bremen, Germany) (15,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%